Human cytotrophoblasts adopt a vascular phenotype as they differentiate. A strategy for successful endovascular invasion? - Zhou, Y. (American Society for Clinical Investigation, 1997)
Establishment of the human placenta requires that fetal cytotrophoblast stem cells in anchoring chorionic villi become invasive. These cytotrophoblasts aggregate into cell columns and invade both the uterine interstitium and vasculature, anchoring the fetus to the mother and establishing blood flow to the placenta. Cytotrophoblasts colonizing spiral arterioles replace maternal endothelium as far as the first third of the myometrium. We show here that differentiating cytotrophoblasts transform their adhesion receptor phenotype so as to resemble the endothelial cells they replace. Cytotrophoblasts in cell columns show reduced E-cadherin staining and express VE-(endothelial) cadherin, platelet-endothelial adhesion molecule-1, vascular endothelial adhesion molecule-1, and alpha-4-integrins. Cytotrophoblasts in the uterine interstitium and maternal vasculature continue to express these receptors, and, like endothelial cells during angiogenesis, also stain for alphaVbeta3. In functional studies, alphaVbeta3 and VE-cadherin enhance, while E-cadherin restrains, cytotrophoblast invasiveness. Cytotrophoblasts expressing alpha4 integrins bound immobilized VCAM-1 in vitro, suggesting that this receptor-pair could mediate cytotrophoblast-endothelium or cytotrophoblast-cytotrophoblast interactions in vivo, during endovascular invasion. In the pregnancy disorder preeclampsia, in which endovascular invasion remains superficial, cytotrophoblasts fail to express most of these endothelial markers (Zhou et al., 1997. J. Clin. Invest. 99:2152-2164.), suggesting that this adhesion phenotype switch is required for successful endovascular invasion and normal placentation.